HUBUNGAN KONSUMSI MAKANAN IBU SELAMA KEHAMILAN DAN PEMBERIAN ASI PERTAMA KALI SETELAH MELAHIRKAN (ASSOCIATION OF MATERNAL FOOD CONSUMPTION DURING PREGNANCY AND THE FIRST TIME BREASTFEEDING AFTER DELIVERY) - Tjetjep Syarif Hidayat; Hermina Hermina; Nurfi Afriansyah (Persagi, 2010)
ABSTRACT Background: Ability to produce breast-milk is to some extent dependent on the storage of material from the mother's food during the prenatal period, as well as on the supply of nutrients from the food she receives during lactation. Objective: To study association of maternal food consumption during pregnancy and the first time breastfeeding after delivery. Methods: We took advantage from a cross-sectional research for Development of Media and Promotional Strategies for Exclusive Breastfeeding in rural and urban West Java, 2006. The analysis is based on 609 mothers who had infants aged 6-12 months in the Bandung city and district, West Java. ‘The first time breastfeeding after delivery’ was identified from the question of ‘how many hours after birth did mother breastfeed her child for the first time’. We used Chi-Square to analyze the association between the mother’s food consumption during prenatal period and the first time breastfeeding after delivery. Results: Mothers who ate more food during pregnancy as much as 1-2 servings per day of pre-pregnancy and the occasional drink of milk to the baby was feeding time less than 3 hours after birth. Whereas mothers who during pregnancy eating just the same as before pregnancy, the first time breastfeeding was longer than 3 hours or even up to 2 days after delivery. The test results obtained was statistically significant difference. Conclusion: Maternal food consumption during pregnancy is significantly associated with the first time breastfeeding after delivery. [Penel Gizi Makan 2010, 33(2): 154-160] Keywords: food consumption, maternal, pregnancy, early breast-milk